2004
DOI: 10.1007/s00595-004-2856-8
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Transforming Growth Factor α Formulation on Aspirin-Induced Ulcer Healing and Oxidant Stress in the Gastric Mucosa

Abstract: These findings suggest that TGF-alpha accelerates the healing process after aspirin-induced gastric injury, and a relationship was observed between this application and the oxidative reactions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 22 publications
0
1
0
Order By: Relevance
“…(26) Similarly, previous investigation suggested decrease of PAS staining during long-term administration of aspirin. (27) The current study showed that diclofenac sodium treatment increased iNOS expression and confirmed by a significant increase in the mean area percentage of iNOS as compared to the control. It was reported that nitric oxide is essential for normal mucosal function and has a role as cytoprotective on the gastrointestinal mucosa.…”
Section: Discussionsupporting
confidence: 68%
“…(26) Similarly, previous investigation suggested decrease of PAS staining during long-term administration of aspirin. (27) The current study showed that diclofenac sodium treatment increased iNOS expression and confirmed by a significant increase in the mean area percentage of iNOS as compared to the control. It was reported that nitric oxide is essential for normal mucosal function and has a role as cytoprotective on the gastrointestinal mucosa.…”
Section: Discussionsupporting
confidence: 68%
“…Several studies showed that administration of growth factors positively effect normal and impaired wound healing (Steed, 1998;Ç elebi et al, 2002;Fujisawa et al, 2003;Gönül et al, 2004). In contrast to skin Table 1 The effects of EGF therapy on the GSH, AA Levels and MPO activity of oral wound strips after incisional operation GSH (lmol/g tissue) AA (mg/g tissue) MPO (U/g tissue) All data are expressed as the mean ± SD * p \ 0.05 in comparison to the untreated groups on the same day wound-healing models, there are few data about the effects of growth factors on healing of the oral mucosa.…”
Section: Discussionmentioning
confidence: 99%
“…Tannin, as a natural product, forms a protective layer in the stomach, increases resistance to injury and has antioxidant and anti-inflammatory properties (de Jesus et al, 2012;Demarque et al, 2018). TGFβ, a growth factor, improves ulcer healing by promoting cell migration, angiogenesis, and extracellular matrix production(Gönül et al, 2004;T. Tanigawa et al, 2005).…”
mentioning
confidence: 99%